Histopathological Changes of Pancreas in Patients with Fibrocalculous Pancreatopathy - Rahman, MT; Rashid, H; Mahtab, H; Kabir, Y (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):186-91.The abstract of this article is available on the PubMed website